Effects of age and sex on outcomes of the Q-Motor speeded finger tapping and grasping and lifting tests-findings from the population-based BiDirect Study - Teismann, Henning; Schubert, Robin; Reilmann, Ralf; Berger, Klaus (Frontiers in Neurology, 2022)
Background. Q-Motor is a suite of motor tests originally designed to assess motor symptoms in Huntington’s disease. Among others, Q-Motor encompasses a finger tapping task and a grasping and lifting task. To date, there are no systematic investigations regarding effects of variables which may affect the performance in specific Q-Motor tests per se. Objective. We investigated effects of age and sex on five selected Q-Motor outcomes representing the two core Q-Motor tasks speeded finger tapping and grasping and lifting in a community sample of middle-aged to elderly adults. Furthermore, we explored effects of the potentially mediating variables educational attainment, alcohol consumption, smoking status, and depressive symptoms. Moreover, we explored inter-examiner variability. Finally, we compared the findings to findings for the Purdue Pegboard test. Methods. Based on a sample of 726 community-dwelling adults and using multipe (Gaussian) regression analysis, we modeled the motor outcomes using age, sex, years in full-time education, depressive symptoms in the past seven days, alcohol consumption in the past seven days, and smoking status as explanatory variables. Results. With regard to the Q-Motor tests, we found that more advanced age was associated with reduced tapping speed, male sex was associated with increased tapping speed and less irregularity, female sex was associated with less involuntary movement, more years of education were associated with increased tapping speed and less involuntary movement, never smoking was associated with less involuntary movement compared to current smoking, and more alcohol consumed was associated with more involuntary movement. Conclusion. The present results show specific effects of age and sex on Q-Motor finger tapping and grasping and lifting performance. In addition, besides effects of education, there also were specific effects of smoking status and alcohol consumption. Overall, the results are in favor of the feasibility and validity of Q-Motor finger tapping and grasping and lifting for large observational studies. Q-Motor tests may generate additional value in particular with regard to clinical conditions such as Huntington’s or Parkinson’s disease.